Jawabanmu

Jawaban paling cerdas!
2014-05-14T18:10:59+07:00
f(x) dibagi (x² - 2x - 3)( bersisa (2x + 1) ⇔ f(x) dibagi (x-3)(x+1) bersisa (2x + 1) ,maka
f(3) = 2(3) +1 = 7 dn f(-1) = 2(-1) + 1 = -1
f(x) dibagi (x²-2x-3) hasil baginya (ax+b) dan sisanya (2x + 1)
S(x) = ax + b  ⇒ S(3)  ⇒ 3a + b = 7
                           S(-1) ⇒ -a  + b = -1 -
                                         4a = 8 ⇒ a = 2 didapatlah b = 1
f(x) = (x²-2x-3)(ax+b) + (2x+1)
       = (x²-2x-3)(2x+1)+(2x+1)
f(-1) = ((-1)² -2(-1) - 3)(2(-1)+1) + (2(-1) + 1)
         = (1 + 2 -3)(-2+1) + (-2+1)
         = 0(-1) -1
         = - 1

1 5 1